Long-term Results of Conservative Treatment, Excision Arthroplasty and Triple Pelvic Osteotomy for the Treatment of Hip Dysplasia in the Immature Dog - Planté, J.; Dupuis, J.; Beauregard, G.; Bonneau, N. H.; Breton, L. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
The long-term efficiency of conservative treatment, excision arthroplasty of the femoral head and neck and triple pelvic osteotomy for the treatment of hip dysplasia in the immature dog were compared using ground reaction forces analysis at the trot. Fourteen hips were re-evaluated for the conservative treatment group, 16 for the triple pelvic osteotomy group and ten for the excision arthroplasty group. Force plate analysis demonstrated that hind limbs belonging to the triple pelvic osteotomy group had, at the trot, a locomotor function similar to the one of normal hind limbs in the control group. At a “similar age”, hind limbs of the conservative group did not show any marked difference from those in the triple pelvic osteotomy and control groups. The dogs of the excision arthroplasty group showed ground reaction forces abnormalities, most probably due to the absence of a coxofemoral joint (decreased peak propulsive force and Fz impulse, compared to triple pelvic osteotomy and control groups). The forelimbs of conservative treatment, excision arthroplasty and triple pelvic osteotomy groups showed a peak propulsive force superior to the one in the control group. This could be an adaptation phenomenon in order to compensate a deficient function of the hind limbs or a habit acquired at a younger age.Force plate analysis has demonstrated that hind limbs treated bilaterally with triple pelvic osteotomy had, at the trot, a locomotor function similar to the one of normal hind limbs from a control group. At a mean age of 4.5 ± 1 years, dogs treated conservatively did not show, at the trot, any marked difference with those treated with triple pelvic osteotomy and with normal dogs. Hind limbs treated with excision arthroplasty showed certain abnormalities most probably due to the absence of a coxofemoral joint such as a significant decrease of peak propulsive force and Fz impulse.
Keywords: Canine hip dysplasia; dog; force plate; triple pelvic osteotomy; excision arthroplasty of the femoral head and neck